Penile duplication or diphallia: case report of a very rare disease - Srivastava, Sandesh; Kumar, Rahul; Sachdeva, Money; Raj, Richa; Singh, Om Prakash (International Journal of Contemporary Pediatrics, 2022)
Diphallia or penile duplication is an extremely rare congenital malformation. The presentation of penile duplication and the number of other associated anomalies, range from a double glans from a penis with no associated anomaly up to complete penile duplication associated with multiple anomalies.